P195 "syndrome z" in the asthma population. (15th November 2017) - Davies, S; Cachada, N; Wharton, S; Turner, AM; Mansur, A
Abstract : Introduction: Current literature demonstrates associations between asthma, obstructive sleep apnoea (OSA) and obesity. Syndrome Z is the occurrence of OSA with the metabolic syndrome, and the relevance of this condition in asthma populations remains unclear. Methods: 192 patients were recruited from a regional severe asthma service and associated respiratory clinics during January 2016-June 2017. 37 had a pre-existing diagnosis of OSA, 116 patients were screened regardless of symptoms, 39 patients with symptoms of OSA were included. Patients underwent an overnight limited channel sleep study and bioelectrical impedance measurements. The groups were split into OSA and no-OSA to compare metabolic profile, associated co-morbidities and body fat composition. Data were analysed using MedCalc version 15. Results: 192 patients with asthma (137 females, 55 males), 173 (90%) had severe asthma, 19 (10%) had non-severe asthma. 37 (19.3%) had pre-existing OSA, 26 of which required Continuous Positive Airway Pressure(CPAP). A total of 97 (51%) had OSA, 58 (30%) had OSA excluded. The OSA group had significantly higher mean Body Mass Index (BMI) (34.8±8.2 versus no-OSA group 28.1±6.0, p<0.001), body fat% (38.2%±11% versus no-OSA group 32.2%±12%, p=0.002), visceral fat rating (12.8±5.1 versus no-OSA group 7.4±4.1, p<0.001) and mean metabolic age (59.5±12.8 years versus no-OSA 44.4±16.7 years, p<0.001). The OSA group also had significantly higher rates of diabetes (OSA 0.25±0.47, no-OSA 0.06±0.23, p=0.005), hypercholesterolaemia (OSA 51/132 (38.6%), no-OSA 9/53 (28.6%), p=0.0046) and hypertension (OSA 50/132 (37.9%), no-OSA 6/53 (10.7%), p=0.0004). There was no significant difference in GORD(p=0.305), rhinosinus disease(p=0.388) or oral corticosteroid requirement(p=0.6896). Asthma Control Questionnaire (ACQ) was significantly higher in OSA 3.3±1.3 compared to the no-OSA group 2.8±1.3, p=0.022 (Apnoea Hypoxia Index (AHI) ≥10) Conclusion: Asthmatics with co-morbid OSA are more likely to have poor asthma control with significantly higher ACQ scores. Additionally, these patients have significantly higher rates of diabetes, dyslipidaemia and hypertension. Routine screening for OSA and metabolic syndrome ("syndrome z") is recommended in asthmatics.